(untitled) (Materiali di Estetica. Terza serie, 2016)
The essay looks back at the most important steps of the relationship between the author and his friend Guido Davide Neri: it is remembered the different way they used to approach the philosophy of history, in particular Marxism, although they were both students of the same professor, Banfi. Their attitude towards the historical background of those years was different too because Neri moved towards socialism, made a theoretical-philosophical consideration, while Papi was more pragmatic and focused on practical policy. The author runs through the philosophical season of 70’s shared and experienced with his friend, when the theoretical background of the University of Milan was focused on the Husserl’s lifeworld, inaugurated in Italy by Enzo Paci.